Pengaruh Corporate Governance terhadap Financial Distress - Alifia Ningrum; Saarce Elsye Hatane (Business Accounting Review, 2017)
The purpose of this study was to know the influence of corporate governance to financial distress. Corporate governance was measured by using board size, board composition, board meeting, woman in board of commissioners, and woman in board of directors. Financial distress was measured by using Altman Z-score. This study also used firm size as control variable. The samples used in this study were 59 companies in the sector of consumer goods and trade listed in Indonesian Stock Exchange in the period of 2010-2015. The hypothesis was tested by using multiple regression analysis with SPSS software version 20. The result of this study revealed that board size, woman in board of directors, and firm size significantly and negatively influenced on financial distress. However, board composition, board meeting, and woman in board of commissioners had no significant influence on financial distress.